Education Should Embrace All Potential: Students’ Reflective Essays on the Meaning of Merdeka Belajar - Roy Martin Simamora; Daniel Pasaribu (Studies in Learning and Teaching, 2023)
This research delves into the perspectives of students regarding the concept of merdeka belajar, as evidenced in their essays for the philosophy of education course. The selected reflection essays are analyzed to explore how students connect their learning experiences to the idea of merdeka belajar. The study aims to uncover how students interpret and apply merdeka belajar to their own learning, through the analysis of forty-five essays submitted for the philosophy of education course, with a focus on thirteen selected students. The research was carried out over the course of May 2022. The analysis reveals seven main themes in the essays, which include the students' understanding of merdeka belajar, their experiences with family and teacher involvement, their views on children's learning abilities, the role of schools in students' lives, experiential learning, diversity and equality in education, and reflections from prospective teachers. The study highlights the importance of promoting merdeka belajar in education and identifies the challenges students face in becoming self-directed learners, along with potential solutions to address these challenges.